Prevalence of mandibular third molar impaction roots position towards mandibular canal based on rood and shehab classification (studies on panoramic radiographs) - Mustamu, Indhira Valerie; Farizka, Intan; Audry Arifin, Sariyani Pancasari; Tjandrawinata, Rosalina; Sekar Palupi, Anggraeny Putri; Tanjung, Rizki (Ikatan Radiologi Kedokteran Gigi Indonesia, 2025)
Objectives: This study aims to determine the prevalence of the position of the impacted mandibular third molar roots in relation to the mandibular canal using a classification by Rood and Shehab. Materials and Methods: This study is a descriptive study with a cross-sectional approach. The samples were 210 left and right third molar impaction tooth mandibular on 105 digital panoramic radiographs at the Radiology Installation, RSGM FKG Usakti, and categorized according to the seven classifications by Rood and Shehab. The interobserver reliability test was conducted using Cohen's Kappa test. The data is presented as frequency and percentages for each type of root position classification. Results: Radiolucent tooth type on the root was the most prevalent at 104 (50%), white line interruption in 28 (13%), narrowing of the mandibular canal in 27 (13%), deflection of the tooth root in 26 (12%), deflection of mandibular canal in 11 (5%), narrowing of the root in 8 (4%), and bifid apex in 6 (3%). Conclusion: The highest prevalence of third molar impaction tooth root position was the radiolucent type at the root, and the lowest was the bifid apex type.